2022
DOI: 10.3390/catal13010086
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Activity and Reusability of F, Sm3+ Co-Doped TiO2/MWCNTs Hybrid Heterostructure for Efficient Photocatalytic Degradation of Brilliant Black Bis-Azo Dye

Abstract: A global freshwater pollution catastrophe is looming due to pollutants of emerging concern (PECs). Conventional water treatment methods are limited in removing PECs such as pharmaceuticals and dye house effluent from aquatic systems. This study provides an effective potential solution by developing an innovative wastewater treatment method based on solar-light-responsive semiconductor-based photocatalysts. A sol-gel synthesis technique was used to produce Fluorine-Sm3+ co-doped TiO2 (0.6% Sm3+) (FST3) photocat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…The efficient recycling of catalysts is a crucial consideration in photocatalysis [60]. In order to reduce waste and ensure sustainable processes, it is desirable to design photocatalysts that maintain consistent photoactivity throughout each cycle [61]. If photocatalysts gradually lose activity over time, they contribute to waste generation during their life cycle.…”
Section: Resultsmentioning
confidence: 99%
“…The efficient recycling of catalysts is a crucial consideration in photocatalysis [60]. In order to reduce waste and ensure sustainable processes, it is desirable to design photocatalysts that maintain consistent photoactivity throughout each cycle [61]. If photocatalysts gradually lose activity over time, they contribute to waste generation during their life cycle.…”
Section: Resultsmentioning
confidence: 99%
“…NiO/TiO 2 composite was prepared by Gul et al [178] for the degradation of orange II dye with 96% degradation within 30 min. Mukonza et al [179] adopted the sol-gel technique and reported Fluorine-Sm 3+ codoped TiO 2 (0.6% Sm 3+ ) catalyst for the degradation of brilliant black BN bisazo dye within 3 hours of simulated solar irradiation. Te total organic carbon removal was 82%.…”
Section: Bismuthmentioning
confidence: 99%